161 Effects of Supplemental Zn Source (sulfate or Bis-glycinate) on Metabolism, Apparent Absorption, and Retention of Zn by Lambs - Deters, Erin L (J Anim Sci, 2021)
To assess bioavailability of bis-glycinate Zn (Plexomin Zn, Phytobiotics), 36 crossbred wethers (34 ± 2 kg) were sorted by body weight into three groups and stagger started on a Zn deplete diet (18.6 mg Zn/kg dry matter [DM]; 22.5% neutral detergent fiber) for 45 d prior to a 15-d metabolism period (10 d adaptation, 5 d collection). On d 46, lambs were randomly assigned to dietary Zn treatments (4 lambs/treatment/group): no supplemental Zn (CON) or 15 mg supplemental Zn/kg DM as Zn sulfate (ZS) or bis-glycinate Zn (GLY). Blood was collected from all lambs on d 1, 44, 56, and 61. Liver, small intestine, and muscle samples were collected after euthanasia on d 61. Liver and intestinal gene expression was determined via quantitative real-time polymerase chain reaction. Data were analyzed using ProcMixed of SAS (experimental unit = lamb; fixed effects = treatment, group, and breed). After 15 d of Zn supplementation, plasma Zn concentrations were greatest for GLY versus CON or ZS (P ≤ 0.01), but tissue Zn concentrations were unaffected (P ≥ 0.15). Liver MT1 expression was approximately 2-fold greater for GLY versus CON or ZS (P ≤ 0.07). Intestinal ZIP4 expression tended or was lesser for ZS or GLY versus CON (P ≤ 0.07) and ZNT1 expression tended to be lesser for ZS versus CON (P = 0.07). Zinc intake, fecal output, retention, and apparent absorption were greater for ZS or GLY versus CON (P ≤ 0.01). Apparent absorption of Zn was -5.1, 12.8, and 15.0% for CON, ZS, and GLY, respectively. Although Zn apparent absorption did not differ between supplemental Zn sources (P = 0.71), differences in post-absorptive metabolism may be responsible for the observed increase in circulating Zn concentrations and liver MT1 expression in GLY supplemented lambs, suggesting improved bioavailability of GLY relative to ZS.